IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH DISCUSSION METHODS AT SMP NEGERI 2 SENTAJO RAYA - Agus Riyanto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the dominant teacher-centered learning process, students’ difficulty in understanding the teacher's explanation, and the use of ineffective learning methods. As a result, the students’ activities became less effective and the students’ learning outcomes became low. Thus, an appropriate learning method was required to solve these problems, in this research, through discussion learning method. This research was a classroom action research conducted at one of SMP Negeri in Kuantan Singingi districts at class 8A, totaling 30 students. The instruments were observation sheets and learning outcome tests. The results showed that there was an increase in students’ activity and learning outcomes in which in cycle I the students’ activity was 78.26% and in cycle II it reached 91.30%. then, the average score of students’ learning outcomes in cycle I was 68.67 with a percentage of completeness of 50%, and the average score in cycle II was 76.11 with classical completeness of 86.67%. Based on these results, it was concluded that learning through the discussion method improved students’ learning outcomes at SMP Negeri 2 Sentajo Raya.